Nonclinical data supporting orphan medicinal product designations in the area of rare infectious diseases. Issue 2 (February 2020) - Sheean, Maria E.; Malikova, Eva; Duarte, Dinah; Capovilla, Giuseppe; Fregonese, Laura; Hofer, Matthias P.; Magrelli, Armando; Mariz, Segundo; Mendez-Hermida, Fernando; Nistico, Robert; Leest, Tim; Sipsas, Nikolaos V.; et al.
Highlights: Non-clinical animal models for rare infectious conditions are reviewed. The article on infections which are either eradicated or very rare in the EU. COMP considerations when assessing medical plausibility is detailed. Clear criteria of the COMP presented to help focus non-clinical research. The Committee for Orphan Medicinal Products (COMP) of the European Medicines Agency (EMA) is responsible for evaluating applications for orphan designation (OMPDs) and for deciding the orphan status at the time of marketing authorization of medicines in the European Union (EU). In this review, we provide transparency regarding assessment criteria and an in-depth review of nonclinical models and data that have been used to support OMPDs. Additionally, we present a literature-based analysis of existing nonclinical models and discuss key features of nonclinical studies, which are considered crucial for the support of future OMPDs. This could not only inform future drug development in rare infectious conditions, but also indicate areas where nonclinical models are indispensable or can be made more efficient. Teaser: This review provides an overview of nonclinical in vivo models that can be used to support orphan designation in selected rare infectious diseases in Europe, with the aim to inform and stimulate the planning of nonclinical development in this area of often neglected diseases.